Antimicrobial resistance, virulence factors and phylogenetic profiles of Vibrio parahaemolyticus in the eastern coast of Shenzhen - Lian, Xian Qiang; Liu, Guo Dong; Huang, Miao Fen; Fan, Qiu Hua; Lin, Zi Dan (Frontiers in Microbiology, 2024)
Vibrio parahaemolyticus (V. parahaemolyticus) is a major food-borne pathogen which causes human gastroenteritis. Since the characteristics of V. parahaemolyticus remain unknown, 220 isolates selected from clinical and environmental samples in Dapeng of Shenzhen were tested for the presence of two hemolysin-expressing genes tdh and trh. Among 27 clinical isolates, 26 carrired the tdh gene, and the other one carried both tdh and trh genes, however neither genes were detected in environmental isolates. Meanwhile, antimicrobial susceptibility profiles revealed the isolates with high frequency of resistance to ampicillin (77.73%) and colistin (71.82%) and medium to streptomycin (57.27%). Genetically, by whole genome sequencing (WGS), comparative genomics studies was performed on isolates from various districts and GenBank. Data analysis showed that antimicrobial resistance genes (ARGs) blaCARB, tet(34) and tet(35) were harbored in all genomes and other ARGs was absent in the genomes of 27 clinical isolates. Besides, little regional difference was observed. As for virulence factors, MAM7, T3SS1, T3SS1 secret effector, T3SS2, T3SS2 secret effector, and VpadF were carried by most isolates. Two isolates from other districts were tdh gene positive which clustered with clinical isolates from Dapeng in the same clade, indicating close genetic distance. This study revealed the widely distribution of V. parahaemolyticus in Shenzhen and the diverse ARGs and virulence genes it carried. Furthermore, pathways that pathogen disseminated through were discussed.